Strategi Diversifikasi Produk Sebagai Upaya Meningkatkan Penjualan Studi Pada CV. Harjaya Enam Makmur - Muhammad Farhan Ramadhanto Muhammad Farhan Ramadhanto; Muhammad Akbar Muhammad Akbar; Redjeki Agoestyowati Redjeki Agoestyowati (JAMBIS : Jurnal Administrasi Bisnis, 2022)
To reach more consumers, develop company value, and win the competition, a product must be attractively different from similar products on the market in terms of size, type, color and model variety, and shapes. This research was conducted at CV Harjaya Enam Makmur with a qualitative approach in which data were obtained through interviews. The results show that the product diversification strategy carried out by CV Harjaya Enam Makmur has a significant effect on its sales volume. In addition, the product diversification strategy also affects the competitiveness, quality of service, and products offered by CV Harjaya Enam Makmur.